Unexpandable lung from pleural disease. Issue 2 (24th October 2017) - Huggins, John T.; Maldonado, Fabien; Chopra, Amit; Rahman, Najib; Light, Richard
ABSTRACT: Unexpandable lung is a common complication of malignant pleural effusions and inflammatory pleural diseases, such as pleural infection (e.g. empyema and complicated parapneumonic effusion) and noninfectious fibrinous pleuritis. Unexpandable lung due to pleural disease may be because of an active pleural process, and is referred to as malignant or inflammatory lung entrapment. An unexpandable lung may also be encountered in the setting of remote pleural inflammation resulting in a mature fibrous membrane overlying the visceral pleura preventing full expansion of the lung. This condition is termed trapped lung and may be understood as a form of defective healing of the pleural space. Trapped lung typically presents as a chronic, stable pleural effusion without evidence of active pleural disease. An unexpandable lung most often manifests itself as an inability of fully expanding the lung with pleural space drainage. Patients will either develop chest pain preventing complete drainage of the pleural space or develop a post‐procedure pneumothorax. Pleural manometry and radiological imaging are useful in the assessment of an unexpandable lung. Pleural manometry can demonstrate abnormal lung expansion during drainage and imaging will demonstrate abnormal visceral pleural thickening found in trapped lung or malignant and inflammatory lung entrapment.